2014
DOI: 10.1088/0004-637x/789/1/4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Structures and Their Generation Mechanisms for Solar Radio Type-I Bursts

Abstract: The fine spectral structures of solar radio type-I bursts were observed by the solar radio telescope AMATERAS. The spectral characteristics, such as the peak flux, duration, and bandwidth, of the individual burst elements were satisfactorily detected by the highly resolved spectral data of AMATEAS with the burst detection algorithm that is improved in this study. The peak flux of the type-I bursts followed a power-law distribution with a spectral index of 2.9-3.3, whereas their duration and bandwidth were dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
2
5
1
Order By: Relevance
“…Strictly speaking, if these small scale heating events are the primary contributor to steady-state coronal heating, it is necessary that α < −2 in order to avoid a situation where the total energy diverges (Hudson 1991). Our findings may be contrasted with the range −3.5 < α < −2.8 found by Mercier & Trottet (1997), Ramesh et al (2012) and Iwai et al (2013Iwai et al ( , 2014. Suresh et al (2017) found that α = −2.23 for very small energy releases observed with the Murchison Widefield Array.…”
Section: Type I Bursts -Histograms Of Burst Amplitude Width and Inter...contrasting
confidence: 99%
“…Strictly speaking, if these small scale heating events are the primary contributor to steady-state coronal heating, it is necessary that α < −2 in order to avoid a situation where the total energy diverges (Hudson 1991). Our findings may be contrasted with the range −3.5 < α < −2.8 found by Mercier & Trottet (1997), Ramesh et al (2012) and Iwai et al (2013Iwai et al ( , 2014. Suresh et al (2017) found that α = −2.23 for very small energy releases observed with the Murchison Widefield Array.…”
Section: Type I Bursts -Histograms Of Burst Amplitude Width and Inter...contrasting
confidence: 99%
“…(e.g. Mercier & Trottet 1997;Iwai et al 2014;Mugundhan et al 2016;Suresh et al 2017). A similar situation is likely to prevail here.…”
Section: Implications Of the Non-thermal Radio Emissionssupporting
confidence: 52%
“…The upper end of this flux range approaches the lower end of the flux range for the power-law fits by Mercier & Trottet (1997) (α ≈ −2.9 to −3.6). Iwai et al (2014), in their observational studies of type-I bursts, also report a power-law index of −2.9 to −3.3. The value of α obtained here is also much lower than the power-law index of −3.5 predicted for the low-energy part of the statistical flare spectrum by Vlahos et al (1995).…”
Section: Peak Flux Densities Of Featuresmentioning
confidence: 94%